RESILIENSI KLIEN PENERIMA MANFAAT PROGRAM PEMBERDAYAAN SOSIAL DI UPTD PUSAT PELAYANAN SOSIAL GRIYA BINA REMAJA (PPSGBR) LEMBANG KABUPATEN BANDUNG BARAT - Muhammad Mahardik Ardiansyah; Ali Anwar Yusuf; Uga Pratama Gunawan (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2023)
Resilience of beneficiary clients of social empowerment programs at UPTD Pusat Pelayanan Sosial Griya Bina Remaja (PPSGBR) Lembang, West Bandung Regency. This study examines how resilient the clients of abandoned children have in UPTD PPSGBR Lembang. Resilience relates to an individual's ability to deal with pressure or difficult situations, in this case abandoned children certainly have pressures and problems in their personal lives. The method used is a qualitative research method of case studies, with the technique of selecting informant purposive sampling. The data collection techniques used are document study techniques, observation and interviews. The results showed that clients of abandoned and out-of-school children who were in UPTD PPSGBR Lembang could be said to be resilient based on the resilience measurement indicators mentioned by Reivich and Shatte (2002) where these aspects consisted of (1) emotional regulation (2) self-control (3) optimism (4) causal analysis (5) empathy (6) self-efficacy and (7) reaching out. The results of measurements carried out in this study show that they have achieved resilience based on the answers of each client who has been asked questions in accordance with aspects related to resilience.